International Seminar on Islamic Civilization and Thoughts (INSIST) 2017: Towards Civilization Sustainability and Universal Peace - PPIK, Pusat Pengajian Ilmu Kemanusiaan (School of Humanities, Universiti Sains Malaysia, 2017)
Islamic civilization was well-known for its significant and tremendous contribution to the advancement of science and technology in its golden era. This was due to the appreciation and effort among the Muslim scholars in the past about translating the teachings of the Quran into a realization as the contents of the Quran very often emphasizes on the importance of knowledge, wisdom, science and adab (ethics) in order for human being to achieve a successful life in this world and in the Hereafter.